Correlation Analysis between Muskrat (Ondatra zibethicus) Musk and Traditional Musk - Xin Shi; Dejun Zeng; Guijun Zhao; Chenglu Zhang; Xiaolan Feng; Chengli Zheng; Diyan Li; Ming Zhang; Hang Jie (Animals, 2023)
Muskrat musk is considered to be a potential substitute for traditional musk. However, little is known about the similarity between muskrat musk and musk, and whether it is related to muskrat age. In this study, muskrat musk (MR1, MR2, and MR3) were from 1, 2, and 3-year-old muskrats, respectively, and white musk (WM) and brown musk (BM) were picked from male forest musk deer. The results indicated that muskrat musk had higher similarity to WM than BM. Further research showed that RM3 had the highest matched degree with WM. By significantly different metabolite analysis, we found that 52 metabolites continue to increase from 1- to 3-year-old muskrats. In total, 7 and 15 metabolites were significantly decreased in RM1 vs. RM2 and RM2 vs. RM3, respectively. Meanwhile, 30 and 17 signaling pathways were observed from increased and decreased metabolites, respectively. The increased metabolites mainly entailed enrichment in amino acid biosynthesis and metabolism, steroid hormone biosynthesis, and fatty acid biosynthesis. In conclusion, muskrat musk from three-year-old muskrat is a relatively good substitute for white musk, and the result also implies that these biological processes of amino acid biosynthesis and metabolism, steroid hormone biosynthesis, and fatty acid biosynthesis are beneficial to the secretion of muskrat musk.